Tuning of the enzyme ratio in a neutral redox convergent cascade: A key approach for an efficient one‐pot/two‐step biocatalytic whole‐cell system. Issue 11 (3rd September 2019) - Ménil, Sidiky; Petit, Jean‐Louis; Courvoisier‐Dezord, Elise; Debard, Adrien; Pellouin, Virginie; Reignier, Thomas; Sergent, Michelle; Deyris, Valérie; Duquesne, Katia; de Berardinis, Véronique; Alphand, Véronique
Abstract: The efficiency of a versatile in vivo cascade involving a promiscuous alcohol dehydrogenase, obtained from a biodiversity search, and a Baeyer–Villiger monooxygenase was enhanced by the independent control of the production level of each enzyme to produce ε‐caprolactone and 3, 4‐dihydrocoumarin. This goal was achieved by adjusting the copy number per cell of Escherichia coli plasmids. We started from the observation that this number generally correlates with the amount of produced enzyme and demonstrated that an in vivo multi‐enzymatic system can be improved by the judicious choice of plasmid, the lower activity of the enzyme that drives the limiting step being counter‐balanced by a higher concentration. Using a preconception‐free approach to the choice of the plasmid type, we observed positive and negative synergetic effects, sometimes unexpected and depending on the enzyme and plasmid combinations. Experimental optimization of the culture conditions allowed us to obtain the complete conversion of cyclohexanol (16 mM) and 1‐indanol (7.5 mM) at a 0.5‐L scale. The yield for the conversion of cyclohexanol was 80% (0.7 g ε‐caprolactone, for the productivity of 244 mg·L −1 ·h −1 ) and that for 1‐indanol 60% (0.3 g 3, 4‐dihydrocoumarin, for the productivity of 140 mg·L −1 ·h −1 ). Abstract : The efficiency of a versatile in vivo cascade involving a promiscuous alcohol dehydrogenase, obtained from a biodiversity search, and a Baeyer–Villiger monooxygenase was enhanced by the independent control of the production level of each enzyme to produce ε‐caprolactone and 3, 4‐dihydrocoumarin. The selection of plasmids based on their copy number (PCN) was the key. Depending on the enzyme and plasmid combinations positive and negative synergetic effects, sometimes unexpected, were observed and exploited.